DO HISTORICAL SALES, FINANCIAL STABILITY, EXTERNAL PRESSURES, AND OTHER FACTORS DRIVE THE PROBABILITY OF FINANCIAL STATEMENT FRAUD? - Ferdinan, Jeremy Emmanuel; Sutrisno, Paulina (Jurnal Akuntansi Trisakti, 2025)
This study aims to obtain empirical evidence regarding factors that can increase the probability of fraudulent financial statements. This research has eight independent variables: financial stability, external pressure, ineffective monitoring, change in auditor, change in director, arrogance, collusion, and history of sales. The research objects in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. Sampling was conducted using a purposive sampling method, which established four sample criteria, and 116 companies were selected as the research sample. The data analysis method used is logistic regression. The results of this study indicate that financial stability and a history of sales increase the likelihood of fraudulent financial statements. However, other independent variables, such as external pressure, ineffective monitoring, changes in auditor, changes in director, arrogance, and collusion, do not increase the probability of fraudulent financial statements. The results of this study provide further insight, particularly for investors and auditors, into how financial stability and sales history can increase the risk of financial statement fraud. Investors are expected to be more cautious and diligent when investing, particularly in companies with substantial asset and sales growth. Likewise, auditors are expected to be more meticulous and thorough when auditing assets and sales to enhance audit quality.